Pencatatan Perkawinan terhadap Kabhin Ghentong Perspektif Peraturan Perundang-Undangan dan Maṣlaḥah (Studi di Desa Lepelle Kecamatan Robatal Kabupaten Sampang): Marriage Registration of Kabhin Ghentong Perspective of Legislation and Maṣlaḥah (Study in Lepelle, Robatal District, Sampang Regency) - Safiatus Zahro; Ali Kadarisman (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
Kabhin ghentong is a term for unregistered marriage practiced by the Lepelle village, Robatal district, Sampang Regency, where marriage registration is carried out after the marriage without any specified time limit. This practice does not fully in accordance with regulated procedures. This study aims to describe and analyze the process of marriage registration for kabhin ghentong from the perspective of Legislation and Maṣlaḥah Regulations. The research method used is empirical legal research that focuses on field research. Data collection techniques involve structured interviews using purposive sampling. The results of the study conclude that kabhin ghentong is a practice of unregistered marriage that registers marriages after marriage without going through regulated procedures. When viewed from the legislation, there is a discrepancy with the Regulation of the Minister of Religious Affairs No. 30 of 2024 on Marriage Registration because it does not fully comply with the procedures for registering marriage intentions, marriage examinations, implementation of marriage contracts and marriage registration. Marriage registration for kabhin ghentong is included in the Maṣlaḥah mursalah because it aims to realize the welfare of society and protect the rights of women and children. This research suggests the need for harmonization between Islamic and civil law to address disparities so that the provisions on marriage registration are complied with by society as a whole.